Enhancement of platelet reactivity and modulation of eicosanoid production by intact erythrocytes. A new approach to platelet activation and recruitment. - Santos, M T (1991)
Erythrocytes are known to influence hemostasis. Bleeding times are prolonged in anemia and corrected by normalizing the hematocrit. We now demonstrate that intact erythrocytes modulate biochemical and functional responsiveness of activated platelets. A two-stage procedure, permitting studies of cell-cell interactions and independently evaluating platelet activation and recruitment within 1 min of stimulation, was developed. Erythrocytes increased platelet serotonin release despite aspirin treatment, enzymatic adenosine diphosphate removal, protease inhibition, or combinations thereof. The data suggested that erythrocyte enhancement of platelet reactivity can reduce the therapeutic effectiveness of aspirin. Erythrocytes metabolically modified platelet arachidonate or eicosapentaenoate release and eicosanoid formation. They promoted significant increases in cyclooxygenase and lipoxygenase metabolites upon platelet stimulation with collagen or thrombin. However, with ionophore, erythrocytes strongly reduced platelet lipoxygenation. These erythrocyte modulatory effects were stimulus-specific. Activated platelet-erythrocyte mixtures, with or without aspirin, promoted 3-10-fold increases in extracellular free fatty acid, which would be available for transcellular metabolism. Erythrocyte-induced increases in free eicosapentaenoate may contribute to antithrombotic and anti-inflammatory effects of this fish oil derivative. These results provide biochemical insight into erythrocyte contributions to thrombosis and hemostasis, and support the concept of thrombus formation as a multicellular event.